2015
DOI: 10.2903/sp.efsa.2015.en-778
|View full text |Cite
|
Sign up to set email alerts
|

Literature review on in vitro and alternative Developmental Neurotoxicity (DNT) testing methods

Abstract: The goal of this systematic review performed under a contract with EFSA was the evaluation of information on assessment methods in the field of developmental neurotoxicity (DNT). Therefore, a systematic and comprehensive literature search and collection of scientific literature and all other relevant grey literature and website information (in English) from past 20 years until mid of April 2014 on the state of the art of in vivo DNT testing methods including novel and alternative non-mammalian models, in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 147 publications
(209 reference statements)
0
35
0
Order By: Relevance
“…The pro-apoptotic alkaloid staurosporine is not an established DNT-positive compound, but has been listed as potential candidate in a systematic review on DNT testing methods 28 . Staurosporine acts mainly as a broad-spectrum protein kinase inhibitor 49 and will most likely interfere with many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-apoptotic alkaloid staurosporine is not an established DNT-positive compound, but has been listed as potential candidate in a systematic review on DNT testing methods 28 . Staurosporine acts mainly as a broad-spectrum protein kinase inhibitor 49 and will most likely interfere with many cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we generated a concentration-response curve (n = 226) for the pro-apoptotic compound staurosporine which has been listed as possible DNT positive compound 28 (Fig. 4B).…”
Section: Clearing and Segmentation Of Slot Imagesmentioning
confidence: 99%
“…The battery of the in vitro assays was applied to hiPSCderived neural stem cells (NSCs) differentiated into a mixed culture of neurons and astrocytes, since this model recapitulates, most of the key processes critical and specific for human brain development including neural progenitor cell commitment, proliferation, migration, neuronal and glial differentiation, synaptogenesis, and neuronal network formation and function [33][34][35]. The readiness of these in vitro methods for regulatory purposes has been recently evaluated based on 13 established semi-quantitative criteria [36].…”
Section: Introductionmentioning
confidence: 99%
“…Do we currently have assays that are ready for chemical screening?" The consensus, based on published literature, the EFSA DNT review (Fritsche et al, 2015) and OECD report (Fritsche, 2016), and data presented by the speakers, indicated that the response to this question depends on the problem formulation. Thus, the answer was "yes" for screening and prioritization, since we have already reached a high level of confidence in a number of process-control based assays (Fig.…”
mentioning
confidence: 99%